2021
DOI: 10.5152/j.aott.2021.20167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malpractice claims on orthopedic and traumatology physicians in Turkey: A survey study

Abstract: Objective This study aimed to investigate the malpractice claims experienced by orthopedic and traumatology physicians and to determine their effects on burnout, job satisfaction, and clinical practice. Methods A questionnaire survey was conducted on orthopedic and traumatology specialists between May 2019 and February 2020. Data collection was carried out via e-survey at “turk-ortopedi” mail group, which is an electronic communication network of orthopedic and traumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Job characteristics, including professional title, professional status, and working hours per week, can be tightly related to job burnout. A survey in Turkey published in 2021 found that burnout level decreased with increasing academic title, and attending physicians were the most exhausted [23]. Working over 40 hours per week was the most important risk factor for burnout in PC physicians in Oman [24].…”
mentioning
confidence: 98%
“…Job characteristics, including professional title, professional status, and working hours per week, can be tightly related to job burnout. A survey in Turkey published in 2021 found that burnout level decreased with increasing academic title, and attending physicians were the most exhausted [23]. Working over 40 hours per week was the most important risk factor for burnout in PC physicians in Oman [24].…”
mentioning
confidence: 98%
“…Doctors who were older than 45 years, on contract, and working in a secondary or tertiary hospital were more likely to have “medium joy in work” than “high joy in work.” Hospital level and doctor’s age influence patients’ choice of care, with higher-level and older doctors being preferred by patients due to more training and practical experience, as well as experience with a higher number of outpatients and inpatients. Lower levels of burnout, greater job satisfaction, and higher joy in work are experienced as age and seniority increase ( Dırvar et al, 2021 ). However, since older doctors generally have higher seniority and positions and have to undertake more clinical and managerial work in the departments, they are under a high state of mental strain.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all the participants in this study, the largest number had a high school level of education. When it comes to academic titles, a study conducted in Turkey implied that the amount of burnout decreases with higher levels of academic titles [ 26 ]. The results of this study were consistent with the results of the study of workplace burnout syndrome, and the joint factors in relation to healthcare workers, where it was shown that those with the lowest education were 1.57 times more prone to emotional exhaustion in relation to those with higher education [ 27 ].…”
Section: Discussionmentioning
confidence: 99%